The EBMT/EHA CAR-T Cell Handbook - Kröger, Nicolaus; Gribben, John; Chabannon, Christian; Yakoub-Agha, Ibrahim; Einsele, Hermann (Springer International Publishing : Imprint: Springer, 2022)
This first open access European CAR-T Handbook, co-promoted by the European Society for Blood and Marrow Transplantation (EBMT) and the European Hematology Association (EHA), covers several aspects of CAR-T cell treatments, including the underlying biology, indications, management of side-effects, access and manufacturing issues. This book, written by leading experts in the field to enhance readers' knowledge and practice skills, provides an unparalleled overview of the CAR-T cell technology and its application in clinical care, to enhance readers' knowledge and practice skills.